Sistem prediksi pengadaan stok bahan baku kayu menggunakan Metode Double Exponential Smoothing (Studi Kasus: CV. Jati Sari) - Wasilaturrohmah, Wasilaturrohmah; Pramuntadi, Andri; Wijaya, Dhina Puspasari; Danianti, Dita (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
In managing the supply of wood raw materials at CV. Jati Sari is still carried out based on the personal experience of business entity owners. Because it is based on personal experience without carrying out in-depth analysis or forecasting, it will create a risk of excess or shortage of stock, making stock management inefficient. The software development method used is the Waterfall method. Double Exponential Smoothing is implemented in this research as a forecasting prediction calculation method. This research produces a prediction system that can produce output in the form of a predicted amount of wood needed as inventory or stock in the warehouse in cubic meters. For manual calculations, the DES method has a prediction calculation result for the 21st period of 4.8 m3. Based on the system testing using black box and white box testing that has been carried out, it can be concluded that the prediction system for procurement of wood raw material stock using the website-based Double Exponential Smoothing method has succeeded well in solving the problem of predicting the amount of wood raw material stock for the next period at CV. Jati Sari.